Inventarisasi Jenis-Jenis Kadal (Sub Ordo Sauria) di Kawasan Hutan Primer, Hutan Sekunder dan Pemukiman di Desa Parek Kacamatan Air Besar Kabupaten Landak - Tri Rima Setyawati, Jepri Noperese Ari Hepi Yanti, (Universitas Tanjungpura, 2019)
Parek Village Air Besar District Landak Regency has two types of forests, primary forest and secondary forest. Parek villagers generally open forests for farming, the activities of these residents can disrupt the existence of the Sauria Sub-Order. The purpose of this study was to determine the species of Sauria Sub-Order in Parek Village.Â The research was conducted by exploration method which was combined with the line transect method in the area of primary forest, secondary forest and settlement. The results of the study found 7 species from the Sauria Sub-Order there are Gonocephalus borneensis, Tachydromus sexlineatus, Cyrtodactylus sp., Hemidactylus sp., Draco sp., Eutropis multifasciata and Apterygodon vittatum which belong to 4 families, Scincidae, Gekkonidae, Agamidae and Lacertidae.